Insights into the rare earth element potential of coal combustion by-products from western Canada. Issue 3 (17th February 2023) - Bishop, Brendan A.; Shivakumar, Karthik Ramachandran; Alessi, Daniel S.; Robbins, Leslie J.
Abstract : Rare earth elements are required for the energy transition and new sources will be needed to meet projected demand. Coal combustion by-products could be a promising, near-term source of rare earth elements. Abstract : Rare earth elements (REE) have been designated as critical minerals by several nations and demand is anticipated to increase as a result of their requirement in clean energy technologies. It has been noted that the current supply of REE may be unable to satisfy this demand, therefore it is becoming increasingly important to find new sources of these metals. Coal combustion by-products (CCBs), including fly and bottom ashes, have emerged potential sources of REE due to their wide availability and environmental and economic incentives for reuse. However, the geochemical composition of the CCBs governs the effectiveness of a given extraction process, therefore they require characterization prior to the development of an efficient, low-cost method for REE recovery. In this study, CCBs from Alberta and Saskatchewan, Canada were investigated using bulk digestions, acid leaching, and sequential extractions to assess western Canadian CCBs as a source of REE. The Ca-rich CCBs from Poplar River contained the highest concentration of REE and nearly 100% of the REE were recovered using acid leaching. Conversely, REE recovery in acid leaches in Si-rich samples from Boundary Dam, Shand, and Alberta ranged from 3 to 65%. Sequential extractions indicated that the REE are primarily hosted in the residual, aluminosilicate phase in all samples consistent with previous studies. Geochemical data for the CCBs in this study were combined with existing data from around the world and subjected to unsupervised machine learning algorithms to assess for potential indicators of REE enrichment. The results indicate REE are correlated with Ti, Si, Zr, Al, and Th and are likely associated with clay and/or detrital minerals. The recovery of REE from CCBs could provide a near-term, environmentally friendly source of critical minerals while addressing the United Nations Sustainable Development Goals 7, 12, and 13.